Lipid peroxidation and decrease on the activities of antioxidant enzymes in experimental infection by Babesia bovis in cattle - Doyle R.L. (2015)
© 2015, Springer-Verlag London.Babesia bovis is one of the causative agents of bovine babesiosis, a disease with high morbidity and mortality in susceptible populations. The aim of this study was to evaluate the occurrence of oxidative stress in cattle experimentally infected with attenuated B. bovis. For that, eight healthy cattle were used and divided into two groups: animals infected with B. bovis (n = 4; group A) and non-infected animals (n = 4; group B). Blood samples of all animals were collected at 0, 7, 11, and 15 days post-infection (DPI) for red blood cells (RBCs) count, and measurement of thiobarbituric acid reactive substance (TBARS) levels in serum (lipid peroxidation) and activity of antioxidant enzymes in whole blood (catalase (CAT) and superoxide dismutase (SOD)). The parasitemia was determined by blood smear evaluation and conventional PCR for B. bovis. Blood smears were negative throughout the experiment; however, infection was confirmed by PCR positive for B. bovis at 15 DPI. A slight reduction on RBC count was observed in cattle of group A at 11 and 15 DPI (P < 0.05). The same animals showed an increased level of TBARS (P < 0.05) at 11 DPI, suggesting lipid peroxidation, while the activities of CAT and SOD decreased (P < 0.05) at 7 and 15 DPI, respectively. Our data support the occurrence of an oxidative/antioxidant imbalance in cattle infected with B. bovis.